DAMPAK KONDISI MAKROEKONOMI TERHADAP EKSPOR GAMBIR INDONESIA KE PASAR INDIA - Mega Amelia Putri; Yelfiarita Yelfiarita (Universitas Galuh, 2022)
Indonesian gambier exports to India undergone a significant change. The impact of macroeconomic conditions on the volume of Indonesian gambier exports to the Indian market has never been analyzed. The aim of study was to examine the response and contribution of the price of gambier, the exchange rate of the rupiah against the US dollar, inflation (general) Indonesia and the volume of world gambier exports to the Indian market using the VAR/VECM analysis approach. Data were analyzed during 1990 to 2020 (30 periods). The results showed that changes in the volume of Indonesian gambier exports to India in the past had a significant effect on the export volume of gambier itself. In the long term, all macroeconomic variables have a significant effect on the volume of Indonesian gambier. The model is for the next 10 years, with a pattern of increasing contribution of macroeconomic variables. The projection results show that the most dominant variability of Indonesian gambier export volume to India is still explained by the Indonesian gambier export volume (EXPIDN) itself with a proportion of 92%. Meanwhile, for macroeconomic conditions, the price of gambier (PRC) contributed 4.95%, inflation (INF) was 1.92%, the rupiah exchange rate against the US dollar (KRS) was 0.79%, and the world gambier volume (WRD) was 0.33%. The results of this analysis can be used as a strategic step in establishing Indonesian gambier trade regulations that stimulate an increase in gambier exports to the world market.